A preliminary survey of freshwater snails in selected barangays in San Miguel, Leyte - Distrajo, Althea An Lurice G. (2017)
In the province of Leyte, gastropod studies are typically that of Oncomelania quadrasi, the intermediate host for Schistosoma japonicum. Thus, other freshwater snail species are mostly overlooked. There were no related studies previously conducted within San Miguel, Leyte. Thus, this study serves as a baseline for taxonomic study of freshwater snails in the municipality. Snails were collected from three stations in selected barangays last March 2017 through intensive snail search and random ring sampling method.